NOVELTY SEEKING TO PREDICT BEHAVIOR INTENTION IN RURAL DESTINATION - Eny Endah Pujiastuti (University of Merdeka Malang, 2020)
Tourists’ perceptions of the destination image, novelty-seeking, tourist satisfaction, and behavior intention are vital for a successful destination marketing. The literature on travel and tourism reveals an abundance of studies on destination image, tourist satisfaction, and behavior intention even though their relationships with novelty-seeking have not been thoroughly investigated in the rural destination. Consequently, the aim of this study is to investigate the influence of destination image on novelty-seeking and satisfaction, which in turn affects the behavior intention of the tourist. The conceptual model was developed on the basis of theoretical and empirical research in the field of tourism; the empirical data were collected in a rural destination. A total of 380 questionnaires were returned and the data were analyzed by using SEM AMOS. Still, the theoretical and managerial implications were drawn based on the findings of the study. Several recommendations were also compiled for future studies.